Efeito de sistemas resinosos e acesso ao conduto na resistência de união de pinos de fibra de vidro cimentados à dentina radicular - Bruno Daleprane (2015)
The type of cement and its curing system, the depth of the root canal and the dentin characteristics may influence the bond strength of root canal posts. This in vitro study evaluated the effect of resin systems and different levels of access to root canal in shear bond strength of fiber glass posts cemented to the dentin. A randomized complete block design used 135 mandibular bovine teeth. The crowns were sectioned at the cemento-enamel junction and the roots received endodontic treatmentand post space preparation for the cementation of fiber glass posts (Reforpost n.3, Angelus) using one of the following systems: RelyX ARC/Adper Scotchbond Multi-Purpose plus (3M ESPE), C&B/All Bond 2 (Bisco) and RelyX U200 (3M ESPE). Each group was further divided into three groups according to the access level to the root canal (coronal, medium, apical), totaling 9 groups (n=15). After posts cementation, the roots were horizontally sectioned to obtain two specimens in each root third, with 1.0 mm thickness. Shear bond strength test was conducted, using 20N loading cell and 0.5mm/min speed. The maximum strength for the post displacement (MPa) was recorded. Then, the specimens were examined under stereomicroscope to characterize the failure mode. Images were obtained by scanning electron microscopy to evaluate the cementation line. The effect of the studied factors and the interactions on the shear bond strength in coronal, middle and apical regions was verified by ANOVA and Tukey´s test (p0.05). When the access to root canal was made on the coronal root third, the cementation system (p=0.790), the root third (p=0.224) and the interaction (p=0.443) did not show significant effect. The bond strength measured only at the apical third showed that the level of access to root canal had a significant effect (p=0.029), but the cementation system (p=0.775) and the interaction (p=0.420) were not significant. When the bond strength was assessed in the same root third of access to the canal, there was a significant effect of root third (p=0.001), but the cementation system (p=0.56) and the interaction (p=0.809) were not significant. Under the experimental conditions, it was concluded that the resin cements exhibited similar shear bond strength. Direct access to the canal promoted superior bond strength on the apical third of root canal, regardless of the resin cement system. The use of luting materials and techniques that facilitate access to the whole canal length for dentin preparation and polymerization of resin systems is recommended.